Participatory Evaluation of Chickpea Production Technology under Central Punjab Conditions (Indian Journal of Extension Education, 2023)
Cluster Front Line Demonstrations (CFLD’s) of chickpea variety PBG7 on 82 locations were conducted to document the economic viability of technology dissemination in central plain conditions of Punjab during 2019-20 and 2020-21 to evaluate chickpea production technology. The demonstrations created an average yield production of 17.80 q/ha, which was 21.03 per cent greater than the traditional farming method (14.70 q/ha). Because of significant variation in the extent of adoption of recommended technology the yield levels were much lower under local practices. Other economic parameters like more B:C ratio (3.63), gross return (57220/ha), and net return (40465.5/ha) were comparatively more under advanced technology demonstrated plots. An average extension gap, technology gap, technology index, and additional returns of chickpea were recorded at 3.09 q/h, 2.2 q/ha, 11% and Rs. 14485/ha, respectively. Variations in agro-climatic factors and management practices were found to be responsible for variations in the technology gap and index percentage which can be reduced by farmer’s participation in adopting new technologies. It is concluded that by opting for new variety and management practices there is a huge scope to increase chickpea production at different strata viz, farmer, district, state and national level.